Cuffless systolic and diastolic blood pressure estimation at the wrist via an optical device: comparison to intra-arterial measurements. (25th November 2020) - Pellaton, C; Vybornova, A; Fallet, S; Marques, L; Grossenbacher, O; De Marco, B; Chapuis, V; Olivero, E; Bertschi, M; Alpert, B.S; Sola, J
Abstract: : The diagnosis and management of hypertension usually requires the estimation of blood pressure (BP) by means of an inflatable cuff. This procedure generates discomfort and limits patient compliance. Cuffless devices capture BP readings without performing any arterial occlusion. We believe that comfortable and cuffless BP monitoring devices can significantly aid in the fight against hypertension and support the expansion of ambulatory and remote patient monitoring programs, provided that these devices provide reliable BP readings. The purpose of this study was to compare the systolic (S) and diastolic (D) blood pressure (BP) estimations from a new optical device at the wrist (figure) against invasive measurements performed on patients scheduled for radial arterial catheterization. The first results from this study were recently published and demonstrated good agreement for the overall study population. Here we report expanded statistical analyses for different population subgroups such as gender, age, body mass index (BMI) and skin color. The study protocol consisted of the simultaneous recording of reflective photo-plethysmographic signals (PPG) from the optical device, and BP values recorded by a contralateral radial arterial catheter. The PPG signals were processed to generate estimates of SBP and DBP. Agreement of paired BP estimations was further calculated in terms of standard deviation (SD) of differences. The mean of differences were systematically zero because BP estimations from the optical device were calibrated for each patient. The table shows that, for the overall population, both SBP and DBP differences SDs were smaller than 8 mmHg (as already published). Furthermore, across different population groups, both genders, all BMIs and all skin colors also resulted in SDs smaller than 8 mmHg. Only patients whose age was above 65 years were associated with a higher SD. For the overall population and most subgroups the new optical technique appears to be capable of replacing more traditional methods of BP estimation. Only the SBP differences for the subgroup of older patients were larger. Additional studies are needed to confirm and expand these very encouraging results. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Aktiia SA